The INTEGRATION OF ETHNO-BEAUTY KNOWLEDGE (ETHNOBOTANY) WITH BIOTECHNOLOGY: FROM TRADITIONAL PLANTS TO MODERN BIOACTIVES - Anggi Qonita; Ursila Indah Pratiwi (Adornata : Ethnobeauty and Wellness Journal, 2025)
This study aims to map recent scientific evidence (2018–2025) regarding the cosmetic and dermatological activities of traditional plants, identify the role of biotechnology in enhancing the effectiveness of natural bioactive compounds, and formulate recommendations for developing modern bioactives rooted in ethno-beauty knowledge. A systematic review method was employed following the PRISMA 2020 guidelines, involving literature searches through Scopus, PubMed, ScienceDirect, and Google Scholar, selection of articles based on inclusion criteria, and thematic analysis of phytochemical data, biological activities, and applied formulation technologies.The results indicate that traditional plants rich in polyphenols, flavonoids, and triterpenoids exhibit significant antioxidant, anti-inflammatory, anti-aging, and skin hydration effects. Empirical evidence further shows that biotechnological innovations such as nanoemulsions, nanosuspensions, liposomes, and controlled delivery systems substantially improve the stability, bioavailability, and efficacy of natural compounds. Centella asiatica emerges as one of the most scientifically validated plants, demonstrating strong skin-regenerative, protective, and anti-photoaging properties when processed through modern formulation technologies. The thematic synthesis highlights that integrating ethnobotanical knowledge, phytochemical profiling, and biotechnology provides a strong scientific foundation for the development of modern, tradition-based cosmetic bioactives. In conclusion, traditional plants hold significant potential as sources of modern cosmetic bioactives, and the application of biotechnology is crucial in optimizing their performance. Further development requires standardized extraction methods, stronger clinical validation, and collaboration between researchers and industry to ensure the creation of safe, effective, and sustainable natural cosmetic products.